Energy Saving by Chopping off Peak Demand Using Day Light - Arindam Kumar Sil; Nirmal Kumar Deb; Ashok Kumar Maitra (Universitas Ahmad Dahlan, 2011)
An artificial intelligent technique has been implemented in this research using real time data’s to calculate how much energy can be chopped from peak load demand. The results are based on real time data that are taken from power delivering centers. These data’s do reflect the present condition of power and a solution to those critical conditions during the peak period. These are done in such a way such that helps in judicious scheduling of load. The time based load scheduling has been done so as to understand the basic criteria for solving power crisis during morning peak and early evening peak. The sunray availability and percentage of load that will use day light saving (DLS) technique has been taken into account in this work. The results shows that about 0.5% to 1% of load can be shedded off from the peak load period which otherwise is reduction of power. Thus it otherwise also means that an equivalent amount of energy is saved which amounts to a large saving of national money. This result is obtained on monthly and even daily basis. Thus this paper justifies DLS gives a new renewable technique to save energy.